P269 Improving the emergency department journey for children with autism and complex needs. (June 2019) - Dann, Lisa; Tormey, Peter; Flanagan, Orla
Abstract : Background: Children with autism and complex needs are frequently seen in the Emergency Department (ED). This can be extremely distressing experience for them. This experience can be improved by several measures, including: staff who are experienced in looking after children with autism/complex needs, minimising their time in ED, providing a quiet, relaxing space for them to wait and the use of social stories and play therapists. However, many ED's remain ill-prepared to manage these children. Aims: To ascertain staff (paediatric and emergency physicians/nurses) comfort and experience levels in managing children with autism or complex needs in the emergency department. To understand parental concerns and obtain their opinion on visits to the Emergency Department- including the most stressful parts and suggestions for change. To affect change within the Emergency Department in order to improve patient and parent experience. Methods: Following ethical approval from the local Clinical Research Ethics Committee, parent questionnaires were distributed. Staff questionnaires will be distributed prior to educational sessions. These will be roughly 1 hour in length and included; Definition of Autism, understanding autism and children with complex needs, a parent discussing their experience and an open question session. Separate study sessions will be held for Paediatric and ED colleagues (doctors and nurses) to maximise attendance. Parental questionnaires were posted to patients of children with moderate to severe autism; intellectual disability or complex needs. These patients were selected from the Community Neurodevelopmental Consultants patient cohort. Results: In total 315 parental questionnaires were distributed. At the time of writing this there have been 40 responses. The results thus far are demonstrating recurring areas which cause the most stress. These areas are: waiting times, small cramped waiting rooms and getting blood tests performed. Staff will be surveyed and education sessions are planned for the next month. Conclusion: The Emergency Department is a stressful environment for everyone but this is particularly true for those with complex needs and autism. Simple measures can be instituted to improve patient and parental experience. We will truly endeavour to implement simple changes, such as educating staff further and a patient alert sticker, to improve the experience of these patients.